Combined glutathione S-transferase T1 and M1 positive genotypes afford protection against Type 2 diabetes in Japanese. (October 2007) - Hori, Masaharu; Oniki, Kentaro; Ueda, Kentaro; Goto, Shuji; Mihara, Shuichi; Marubayashi, Toru; Nakagawa, Kazuko
Introduction: Diabetes mellitus is associated with an increased production of reactive oxygen species and a reduction in antioxidant defenses. The aim of this study is to determine the association between the incidence of Type 2 diabetes and gene polymorphisms of glutathione S -transferase ( GST ), which modulates oxidative stress.Materials & Methods: The associations between the incidence of Type 2 diabetes and the GSTT1 and GSTM1 genotypes were analyzed in 469 Japanese participants in a health-screening program.Results: The clinical characteristics and smoking status were obtained from the health screening record. The incidence of diabetes was 1.5-fold higher in the GSTT1 and GSTM1 null ( - ) genotype than the GSTT1 and GSTM1 present (+) genotype, respectively. Although the effect of each null genotype was not significant, the combined GSTT1+/GSTM1+ genotypes conferred a significant reduction in risk of diabetes in comparison with the other combinations of genotypes (adjusted odds ratio [OR]: 0.30; 95% confidence interval [CI]: 0.12––0.71). In stratified analyses by smoking status, the incidence of diabetes was significantly higher in never-smokers with the GSTT1- genotype than those with the GSTT1+ genotype (OR: 2.85; 95% CI: 1.17––6.94) and increased significantly in current smokers (OR: 5.91; 95% CI: 1.96––17.88). The effect of the GSTM1- genotype was significant only in current smokers.Conclusion: This study demonstrated that the GSTT1- and GSTT1- / GSTM1- genotypes are independent risk factors for development of Type 2 diabetes regardless of the smoking status of the patient, and that these genotypes and current smoking were interactively associated with the incidence of Type 2 diabetes.